Hepatitis B surface antigen reduction is associated with hepatitis B core-specific CD8+ T cell quality - Takahama, Shokichi; Yoshio, Sachiyo; Masuta, Yuji; Murakami, Hirotomo; Sakamori, Ryotaro; Kaneko, Shun; Honda, Takashi; Murakawa, Miyako; Sugiyama, Masaya; Kurosaki, Masayuki; Asahina, Yasuhiro; Takehara, Tetsuo; et al. (Frontiers in Immunology, 2023)
This is a provisional file, not the final typeset article Despite treatment, hepatitis B surface antigen (HBsAg) persists in patients with chronic hepatitis B (CHB), suggesting the likely presence of the virus in the body. CD8 + T cell responses are essential for managing viral replication, but their effect on HBsAg levels remains unclear. We studied the traits of activated CD8 + T cells and HBV-specific CD8 + T cells in the blood of CHB patients undergoing nucleos(t)ide analog (NUC) therapy.For the transcriptome profiling of activated CD8 + T cells in peripheral blood mononuclear cells (PBMCs), CD69 + CD8 + T cells were sorted from six donors, and single-cell RNA sequencing (scRNA-seq) analysis was performed. To detect HBV-specific CD8 + T cells, we stimulated PBMCs from 26 donors with overlapping peptides covering the HBs, HBcore, and HBpol regions of genotype A/B/C viruses, cultured for 10 days, and analyzed via multicolor flow cytometry.scRNA-seq data revealed that CD8 + T cell clusters harboring the transcripts involved in the cytolytic functions were frequently observed in donors with high HBsAg levels. Polyfunctional analysis of HBV-specific CD8 + T cells utilized by IFN-g/TNFa/CD107A/CD137 revealed that HBcore-specific cells exhibited greater polyfunctionality, suggesting that the quality of HBV-specific CD8 + T cells varies among antigens. Moreover, a subset of HBcore-specific CD8 + T cells with lower cytolytic potential was inversely correlated with HBsAg level.Our results revealed a stimulant-dependent qualitative difference in HBV-specific CD8 + T cells in patients with CHB undergoing NUC therapy. Hence, the induction of HBcore-specific CD8 + T cells with lower cytolytic potential could be a new target for reducing HBsAg levels.